2014
DOI: 10.1016/j.cplett.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Microwave frequency modulation to enhance Dissolution Dynamic Nuclear Polarization

Abstract: International audienceHyperpolarization by Dissolution Dynamic Nuclear Polarization is usually achieved by monochromatic microwave irradiation of the ESR spectrum of free radicals embedded in glasses at 1.2 K and 3.35 T. Hovav et al. (2014) have recently shown that by using frequency-modulated (rather than monochromatic) microwave irradiation one can improve DNP at 3.35 T in the temperature range 10-50 K. We show in this Letter that this is also true under Dissolution-DNP conditions at 1.2 K and 6.7 T. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 32 publications
3
127
0
Order By: Relevance
“…Another method that may be adopted is the use of scavengers such as sodium ascorbate during the dissolution process to reduce nitroxide free radicals such as 4-oxo-TEMPO can prolong the hyperpolarization lifetime of nuclear spins. [43] Other ways that may further boost the DNP enhancement levels or expedite the polarization transfer process include 1 H-13 C cross polarization, [27,44,45] microwave frequency modulation during DNP irradiation, [46] appropriate choice of free radicals, [47][48][49][50] lanthanide doping, [16,29,38,51] 13 C enrichment, [52] and deuteration [53] of the glassing matrix in the DNP sample. Finally, we would like note that the total cost of the commercial parts and machined pieces of our homebuilt hyperpolarizer system, with the exclusion of the cost of the widebore superconducting magnet and dedicated NMR spectrometer, is only slightly under USD95,000.00-a small fraction of the cost of the commercial HyperSense polarizer (Oxford Instruments, UK) and the clinical SpinLab hyperpolarizer (GE Healthcare, WI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method that may be adopted is the use of scavengers such as sodium ascorbate during the dissolution process to reduce nitroxide free radicals such as 4-oxo-TEMPO can prolong the hyperpolarization lifetime of nuclear spins. [43] Other ways that may further boost the DNP enhancement levels or expedite the polarization transfer process include 1 H-13 C cross polarization, [27,44,45] microwave frequency modulation during DNP irradiation, [46] appropriate choice of free radicals, [47][48][49][50] lanthanide doping, [16,29,38,51] 13 C enrichment, [52] and deuteration [53] of the glassing matrix in the DNP sample. Finally, we would like note that the total cost of the commercial parts and machined pieces of our homebuilt hyperpolarizer system, with the exclusion of the cost of the widebore superconducting magnet and dedicated NMR spectrometer, is only slightly under USD95,000.00-a small fraction of the cost of the commercial HyperSense polarizer (Oxford Instruments, UK) and the clinical SpinLab hyperpolarizer (GE Healthcare, WI).…”
Section: Resultsmentioning
confidence: 99%
“…This used Bruker NMR magnet was energized to a field of 6.423 T, corresponding to a proton Larmor frequency of 273. 46 MHz and an ESR frequency of 180 GHz.…”
Section: A Polarizer Magnetmentioning
confidence: 99%
“…More recently Hovav et al [55] have shown that frequency modulation could improve DNP at 3.35 T in the temperature range 10-50 K, close to the d-DNP conditions. We have recently shown that the same approach is also beneficial at lower temperatures (T = 1.2 K) and at higher magnetic fields (B 0 = 6.7 T) [56]. When microwave frequency modulation is applied, the DNP-active fraction of the ESR line is no longer determined solely by the polarizing agents concentration.…”
Section: Applying Microwave Frequency Modulationmentioning
confidence: 98%
“…25 The hyperpolarized sample is then quickly dissolved using superheated D 2 O and transferred to an NMR magnet through a magnetic tunnel, 26 where it is rapidly injected into an equilibrated protein−ligand solution ( Figure 1). The excitation of hyperpolarized water can lead to massive radiation damping (RD) and demagnetizing distant dipolar field effects.…”
mentioning
confidence: 99%